The Differing Roles of Cognitive Empathy and Affective Empathy in the Relationship Between Trait Anger and Aggressive Behavior: A Chinese College Students Survey - Jiang, Qi (Journal of interpersonal violence, 2021)
Empathy is essential for effective social interaction. People often express the belief that empathy is closely related to aggressive behavior, but empirical data has challenged this assumption. However, there is a lack of research that focuses on the role of empathy in the relationship between trait anger and aggressive behavior. The current research focuses on the roles that different components of empathy have performed in the combinations of trait anger-hostile cognition-aggressive behavior link and attempt to identify, with reference to Integrated Model of Emotion Processes and Cognition in Social Information Processing, at which step this may occur. Participants included 663 undergraduate students who completed self-report measures of Trait Anger Scale, Aggressive Behavior Questionnaire, the Interpersonal Reactivity Index, and the Reactive-Proactive Aggression Questionnaire. Results from correlation analysis show that there is no significant correlation between cognitive empathy and aggressive behavior (r = −.06) but do however suggest a significant correlation between affective empathy and aggressive behavior (r = −.19). Results from structural equation modeling reveal that different components of empathy perform different roles in relation to aggressive behavior. The moderated mediating model analysis results show that cognitive empathy played a moderating role in both the direct effect and the first stage of the mediating model of trait anger-hostile cognition-aggression behavior. The results of multiple mediation model analysis demonstrate that affective empathy only played a partial mediating role between hostile cognition and aggressive behavior. This study contributes to understanding of Social Information Processing Models (SIPMs) and provides insight into the relationship between empathy and aggressive behavior.